2021
DOI: 10.18632/aging.202831
|View full text |Cite
|
Sign up to set email alerts
|

Seven interferon gamma response genes serve as a prognostic risk signature that correlates with immune infiltration in lung adenocarcinoma

Abstract: Interferon-gamma (IFN-γ) plays a complex role in modulating tumor microenvironment during lung adenocarcinoma (LUAD) development. In order to define the role of IFN-γ response genes in LUAD progression, we characterized the gene expression, mutation profile, protein-protein interaction of 24 IFN-γ response genes, which exhibited significant hazard ratio in overall survival. Two subgroups of LUAD from the TCGA cohort, which showed significant difference in the survival rate, were identified based on the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Moreover, MT2A expression is controversial in lung cancer. A recent study has found that high expression of MT2A is associated with poor prognosis of lung adenocarcinoma [ 23 ]. However, a previous study has found that MT2A expression levels in lung cancer tissues are significantly downregulated compared to paracancerous tissues [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, MT2A expression is controversial in lung cancer. A recent study has found that high expression of MT2A is associated with poor prognosis of lung adenocarcinoma [ 23 ]. However, a previous study has found that MT2A expression levels in lung cancer tissues are significantly downregulated compared to paracancerous tissues [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Yao et al. constructed the signature of seven IFN-γ-related lncRNAs to assess prognosis in patients with lung adenocarcinoma, in which the high-risk group had a worse prognosis and was associated with high levels of tumor-promoting immune cells ( 51 ). Liu et al.…”
Section: Discussionmentioning
confidence: 99%
“…CD74 (MHC class II invariant chain) is a nonpolymorphic type II transmembrane glycoprotein which not only plays an important role in liver fibrosis and Alzheimer's disease but also participates in tumor progression ( Su et al., 2017 ). It was shown that CD74, as an interferon gamma response gene, was a prognostic risk marker related to immune infiltration of LUAD ( Yao et al., 2021 ). CD74 interacted with CD44 and enhanced the occurrence and metastasis of breast cancer through RHOA-mediated cofilin phosphorylation ( Liu et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%